Experimental verification of a crystal plasticity-based simulation framework for predicting microstructure and geometric shape changes: Application to bending and Taylor impact testing of Zr. (October 2020) - Vasilev, Evgenii; Zecevic, Miroslav; McCabe, Rodney J.; Knezevic, Marko
Highlights: Mechanical behavior and microstructural evolution of high-purity zirconium deforming plastically over 10 −3 /s to 10 5 /s strain rates are studied. Compression, tension, beam bending, and Taylor cylinder impact tests along with EBSD characterization are carried out. A linked grain-scale to polycrystalline aggregate-scale to FEM macro-scale modeling framework is used to simulate the experiments. Geometry and texture along with twin volume fraction have been measured to experimentally verify the crystal plasticity model. Anisotropic material flow induced by microstructural changes of texture and twinning is predicted during the tests. Abstract: This paper is concerned with experimental verification of a recently developed multi-scale simulation framework for plastic deformation of metallic materials from quasi-static to impact deformation conditions. The framework is a visco-plastic self-consistent (VPSC) polycrystalline model embedded in an implicit finite element method (FE-VPSC) to provide a microstructure-sensitive constitutive response at each material point. Each material point of the FEM model is a polycrystalline aggregate with crystallographic deformation mechanisms operating at the single crystal scale with their evolving activity based on a dislocation density-based hardening law and texture. Four beams and three cylinders machined in different orientations from a textured plate of high-purity zirconium are tested quasi-statically in 4-point bending and at speeds of 100 m/s, 170 m/s and 243 m/s during Taylor impact tests, respectively. The variation in dimensional changes resulting from different sample orientations in the plate with respect to loading directions is measured for each sample. Moreover, texture and twinning characterization is performed using electron backscattered diffraction (EBSD). The deformation processes and underlying evolution of microstructure are successfully simulated using the FE-VPSC framework. In doing so, the model parameters are optimized and validated across a broad range of strain rates and temperatures. Simulation results in terms of geometrical changes and microstructural evolution are compared with the experimental measurements. The model predicts anisotropic material flow resulting from the hard-to-deform crystallographic directions, the development of gradients in texture and twinning through the geometries, tension–compression asymmetry, as well as the extent of plasticity under impact.